2023
DOI: 10.1002/anie.202305081
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Mediated Ring Expansion of Indoles and Pyrroles with Chlorodiazirines: Synthetic Methodology and Thermal Hazard Assessment

Abstract: We demonstrate that arylchlorodiazirines serve as photo‐activated halocarbene precursors for the selective one‐carbon ring expansion of N‐substituted pyrroles and indoles to the corresponding pyridinium and quinolinium salts. Preliminary investigations indicate that the same strategy also enables the conversion of N‐substituted pyrazoles to pyrimidinium salts. The N‐substituent of the substrate plays an essential role in: (1) increasing substrate scope by preventing product degradation, (2) enhancing yields by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 65 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…The scope and limitations of our protocol were explored (Figure 4). First, we found that several N-activators were compatible with our one-pot procedure, including PhCOCl (1), Boc 2 O (13), CbzCl (24), base-sensitive FmocCl (25), AllocCl (26), and even TrocCl (27), with a modest yield. Alkylpyridines gave satisfactory results affording the desired diazepines, although the yield drops when the pyridine is substituted with a benzyl group in the 4-position (28−33).…”
Section: Journal Of the American Chemicalmentioning
confidence: 90%
See 1 more Smart Citation
“…The scope and limitations of our protocol were explored (Figure 4). First, we found that several N-activators were compatible with our one-pot procedure, including PhCOCl (1), Boc 2 O (13), CbzCl (24), base-sensitive FmocCl (25), AllocCl (26), and even TrocCl (27), with a modest yield. Alkylpyridines gave satisfactory results affording the desired diazepines, although the yield drops when the pyridine is substituted with a benzyl group in the 4-position (28−33).…”
Section: Journal Of the American Chemicalmentioning
confidence: 90%
“…Over the past years, many elegant strategies have emerged aiming at editing aromatic skeletons by inserting, deleting, , or swapping atoms in a short amount of time and steps (Figure B). Thus, one could rapidly evaluate the potential interest of drug analogues by interchanging the nature of one (or more) aromatic ring(s).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, one‐carbon ring expansion of indoles and pyrroles, achieved via a [2+1] cycloaddition‐fragmentation‐aromatization sequence, represents a straightforward approach to valuable quinolines and pyridines (Figure 1C). [8a–o] One key design of this transformation lies in the in situ generation of an electrophilic carbene intermediate that bears a suitable leaving group. As pioneers in this field, Ciamician and Dennstedt first realized the transformation of pyrroles into 3‐chloropyridines with chloroform‐derived chlorocarbene, yet low reaction yield and poor functional group tolerance limit its practical implementation [8e,f] .…”
Section: Figurementioning
confidence: 99%
“…As pioneers in this field, Ciamician and Dennstedt first realized the transformation of pyrroles into 3‐chloropyridines with chloroform‐derived chlorocarbene, yet low reaction yield and poor functional group tolerance limit its practical implementation [8e,f] . Aimed to enhance the reaction compatibility and diversify the azine skeletons, continuous efforts have been devoted to the development of new carbene sources [8g–o] . Especially, recent works have made significant progress by employing halodiazoesters or chlorodiazirines as carbene precursors [8l–o] .…”
Section: Figurementioning
confidence: 99%
“…Transforming parent molecular frameworks into structurally related compounds through the insertion of single atoms has gained increased attention over the last decades, further expanding the synthetically accessible chemical space. Through the insertion of heteroatoms such as oxygen or nitrogen into abundant frameworks, rapid access to a diverse array of shape-similar targets with modulated pharmacokinetic properties is possible. Additionally, applying these strategies to diversify target structures at a late stage obviates time-consuming de novo syntheses and directly affords biologically interesting heterocycles expanding available medicinal chemistry libraries. , Recently, various methods were developed to interconvert widely encountered scaffolds such as indoles and pyrroles into the corresponding carbon-atom extended frameworks, including quinolines and pyridines. Strategies to afford the corresponding N , N -heterocycles were also disclosed, however, these either depend on harsh reaction conditions and present a limited scope or rely on the use of protecting group strategies that require a separate prefunctionalization step (Figure a). , In addition, the strategically related development of a nitrogen atom insertion into pyrroles to access the corresponding pyrimidine motifs is underdeveloped and was showcased for only two selected examples, 2,3,4,5-tetraphenyl-1 H -pyrrole (Figure b) , and ethyl 4-(4-methoxyphenyl)-2,5-dimethyl-1 H -pyrrole-3-carboxylate …”
mentioning
confidence: 99%